2016
DOI: 10.1007/s12264-016-0071-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Epigenetic Regulation in Injury-Mediated Neuronal Dendritic Plasticity

Abstract: Injury to the nervous system induces localized damage in neural structures and neuronal death through the primary insult, as well as delayed atrophy and impaired plasticity of the delicate dendritic fields necessary for interneuronal communication. Excitotoxicity and other secondary biochemical events contribute to morphological changes in neurons following injury. Evidence suggests that various transcription factors are involved in the dendritic response to injury and potential therapies. Transcription factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…Neuroplasticity may also occur in various practices in our daily life, for example, when we try to learn a new skill or memorize a new information, persistent functional changes keep happening in our brain 25 . It may also occur under the condition of compensation for neural injury 26 .…”
Section: Neuroplasticity Following Ischemic Strokementioning
confidence: 99%
“…Neuroplasticity may also occur in various practices in our daily life, for example, when we try to learn a new skill or memorize a new information, persistent functional changes keep happening in our brain 25 . It may also occur under the condition of compensation for neural injury 26 .…”
Section: Neuroplasticity Following Ischemic Strokementioning
confidence: 99%
“…A variety of diseases arising from inflammation, internal or external damages, alter epigenetic regulations, including DNA methylation, histone methylation, and histone acetylation. Evidence has demonstrated that epigenetic regulations play an essential role in mediating spinal cord plasticity and neuronal differentiation during SCI [17][18][19]. The epigenetic modification processes are associated with mechanisms that underlie the repair and therapy of SCI.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…To date, most of the literature on adult spinal cord plasticity has focused on injury outcomes (Wang, Li, et al, 2016;), pain (Jiang et al, 2017;Zhao et al, 2017), or disease (Martin & Wong, 2013;Miranpuri et al, 2017), with limited data providing a developmental profile of epigenetic mechanisms associated with neurobehavioral plasticity in the spinal cord. Understanding these mechanisms may shed insight on why the spinal cord is most responsive to environmental input during early development, as epigenomics is a known moderator of environmental input and future behavioral states, including increased disease states (e.g., Cheng et al, 2022;McGowan et al, 2009;Roth et al, 2009;Szyf, 2009;Weaver et al, 2004).…”
Section: Introductionmentioning
confidence: 99%